2009
DOI: 10.1097/01.ogx.0000349781.28386.c8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fertility Drugs and Risk of Ovarian Cancer: Danish Population Based Cohort Study

Abstract: Objective To examine the effects of fertility drugs on overall risk of ovarian cancer using data from a large cohort of infertile women. Design Population based cohort study. Setting Danish hospitals and private fertility clinics. Participants 54 362 women with infertility problems referred to all Danish fertility clinics during 1963-98. The median age at first evaluation of infertility was 30 years (range 16-55 years), and the median age at the end of follow-up was 47 (range 18-81) years. Included in the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…What is becoming increasingly clear is that, contrary to the international consensus recommendation, 1,2 metformin is a very suitable alternative to clomiphene as a first‐line ovulation induction treatment for non‐obese women with anovulatory PCOS. In fact, metformin carries some potential advantages over clomiphene, including no known adverse endometrial effect (whilst endometrial thinning could reduce embryo receptivity for some women using clomiphene 19,20 ), no known increase in multiple pregnancy rate (unlike that associated with clomiphene) and thus no requirement for inconvenient and costly monitoring of ovulation induction cycles by serum oestradiol measurements with access to follicular ultrasound scanning (widely regarded as essential for clomiphene), and no concern over long‐term adverse effects on the ovaries (contrasting with the lingering concern over increased risk of ovarian cancer seen in some cohort studies of women using clomiphene, particularly serous ovarian cancer 21 and amongst those using long treatment courses 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…What is becoming increasingly clear is that, contrary to the international consensus recommendation, 1,2 metformin is a very suitable alternative to clomiphene as a first‐line ovulation induction treatment for non‐obese women with anovulatory PCOS. In fact, metformin carries some potential advantages over clomiphene, including no known adverse endometrial effect (whilst endometrial thinning could reduce embryo receptivity for some women using clomiphene 19,20 ), no known increase in multiple pregnancy rate (unlike that associated with clomiphene) and thus no requirement for inconvenient and costly monitoring of ovulation induction cycles by serum oestradiol measurements with access to follicular ultrasound scanning (widely regarded as essential for clomiphene), and no concern over long‐term adverse effects on the ovaries (contrasting with the lingering concern over increased risk of ovarian cancer seen in some cohort studies of women using clomiphene, particularly serous ovarian cancer 21 and amongst those using long treatment courses 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…95%CI: 1.95-13.75). In a large cohort of over 54,000 infertile women, Jensen et al observed no excess risk for invasive ovarian cancer in any of the groups exposed to fertility drugs [39].…”
Section: Ovarian Cancermentioning
confidence: 98%
“…These two studies prompted several other investigations, including cohort studies in Australia, 18,48 Israel, 14,16,49,50 the United States, 28,51 the Netherlands, 29 the United Kingdom, 52,53 Denmark, 54 and Sweden. [55][56][57] Most of these studies failed to provide confirmation of a link between fertility drug use and ovarian cancers.…”
Section: Cohort Studiesmentioning
confidence: 99%